Quantitative evaluation of tuberculosis activity - Araújo, Iberê [UNESP]; Pina, Diana [UNESP]; Alvarez, Matheus [UNESP]; Pavan, Ana Luiza [UNESP]; Pereira, Paulo Câmara Marques [UNESP]; Marrone, Sérgio [UNESP]; Miranda, José Ricardo [UNESP] (My University, 2013)
Tuberculosis (Tb) is one of oldest disease and still very common in underdeveloped countries. The pathology of Tb is mostly determined by the intense inflammatory process and scarring of the lung. Identify these findings rightly is very important to choose the right conduct for patient and also to evaluate efficiency and sequelae of the treatment used. For this study we evaluated four high resolution tomography computerized (HRTC) for patients who had Tb in activity and two healthy person as control using specific algorithm to quantify the inflammation process, fibrosis, emphysema, and cavitations. Quantifier algorithms were developed to distinguish abnormal regions in a preselected lung field (manually), being -920HU(Hounsfield Unit) for emphysema and cavitations and 70HU for fibrosis and inflammation process. The presented algorithm is a breakthrough in lowering the bias of the subjectivity of visual assessment, standardizes the findings objectively and streamlines de clinical research in Tb. Primary evaluations of these HRTC allowed yields that algorithm did not confuse abnormal regions with normal structures in lung. Furthermore, we have found as preliminary results that patients with Tb in activity had around 13,06% of the lung with Inflammation Process or Fibrosis and 16,37% with Emphysema or Cavitations. As future objectives, we aim to set up the differentiation of these onsets, then we will be able to specify the Tb activity, compare the effectiveness of treatments and also draw a quantitative overview of the disease.